ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA PADA MATERI SPLTV KELAS X SMK NEGERI 1 TOMA TAHUN PEMBELAJARAN 2021/2022 - Surven(1); Antonius Sarumaha(2); Hestu Tansil La’ia(3) (Universitas Nias Raya, 2022)
This research is motivated by the low ability of students to understand mathematical concepts. This study aims to 1) describe students' ability to understand mathematical concepts on SPLTV material, 2) describe students' difficulties in completing tests of students' ability to understand mathematical concepts on SPLTV material. This research uses qualitative research with descriptive research approach. The number of informants in this study were 15 people. The data were analyzed by data reduction, data presentation and conclusion drawing. The technique of collecting research data is through an ability test for understanding mathematical concepts and interviews. The research findings obtained (1) students are not able to present SPLTV concepts or definitions, (2) students are not able to distinguish systems of equations that are included in SPLTV and not included in SPLTV, (3) students are not able to present SPLTV concepts in various forms of mathematical representation, especially formulating equations. or create a mathematical model, (4) students have difficulty developing the adequacy of the data or information contained in the problem to be able to solve the problem, (5) students have difficulty using or choosing the settlement procedure used in SPLTV such as the elimination method and the substitution method, (6) students are not able to apply the SPLTV concept in solving contextual problems. So it can be concluded that the students' ability to understand mathematical concepts is still relatively low. Through this research, it is suggested that every mathematics teacher can further develop students' ability to understand mathematical concepts. In addition, students are expected not to rely on rote memorization, but prioritize understanding the concept of SPLTV material so that they can apply the concept in various situations.